LAP-VEGaS Practice Guidelines for Reporting of Educational Videos in Laparoscopic Surgery: A Joint Trainers and Trainees Consensus Statement. Issue 6 (December 2018) - Celentano, Valerio; Smart, Neil; McGrath, John; Cahill, Ronan A.; Spinelli, Antonino; Obermair, Andreas; Hasegawa, Hirotoshi; Lal, Pawanindra; Almoudaris, Alex M.; Hitchins, Charlotte R.; Pellino, Gianluca; Browning, Matthew G.; et al.
Abstract : Objective: Consensus statement by an international multispecialty trainers and trainees expert committee on guidelines for reporting of educational videos in laparoscopic surgery. Summary of Background Data: Instructive laparoscopy videos with appropriate exposition could be ideal for initial training in laparoscopic surgery, but there are no guidelines for video annotation or procedural educational and safety evaluation. Methods: Delphi questionnaire of 45 statements prepared by a steering group and voted on over 2 rounds by committee members using an electronic survey tool. Committee selection design included representative surgical training experts worldwide across different laparoscopic specialties, including general surgery, lower and upper gastrointestinal surgery, gynecology and urology, and a proportion of aligned surgical trainees. Results: All 33 committee members completed both the first and the second round of the Delphi questionnaire related to 7 major domains: Video Introduction/Authors' information; Patient Details; Procedure Description; Procedure Outcome; Associated Educational Content; Peer Review; and Use in Educational Curriculae. The 17 statements that did not reach at least 80% agreement after the first round were revised and returned into the second round. The committee consensus approved 37 statements to at least an 82% agreement. Conclusion: Consensus guidelines on how to report laparoscopic surgery videos for educational purposes have been developed. We anticipate that following our guidelines could help to improve video quality. These reporting guidelines may be useful as a standard for reviewing videos submitted for publication or conference presentation.